Cloning of ARE-containing genes by AU-motif-directed display. - Dominguez, O; Ashhab, Y; Sabater, L; Belloso, E; Caro, P; Pujol-Borrell, R (My University, 1998)
A procedure suitable for cloning labile mRNAs that contain AU motifs is presented (AU-DD). These motifs are regulatory sequences within the so-called AU-rich elements (AREs) often found in 3' untranslated regions of genes such as cytokines, proto-oncogenes, and transcription factors. AU-DD is an AU-motif-directed differential display that permits the identification of ARE-containing genes differentially expressed after cell activation. It has been applied to peripheral blood monocytes and a T cell clone to isolate 59 cDNA fragments associated to activation. Fourteen percent of isolated fragments belong to already known genes that certainly are cytokines and transduction/transcription factors. The remaining 86% correspond to unknown genes of which 92% have been confirmed to be differentially expressed. These data demonstrate the efficiency of the system and support the notion that numerous genes falling into those categories remain unidentified and that they can be cloned by this method.